HYPOCRYSIS IN THE SHORT STORY ENTITLED AKHIRNYA KITA SEMUA MENJADI MALING BY ZAIDINOOR - Christina Wahyuningsih; Harjito; Ika Septiana (Literature and Literacy, 2024)
Hypocrisy in literature often reflects the complexity of human nature as well as broader social dynamics, providing critical insight into culture and social structure. This research aims to identify human nature and broader social dynamics, and describe hypocrisy in the short story "Akhirnya Kita Semua Menjadi Maling" by Zaidinoor. The research uses a qualitative approach with a descriptive design. This research uses a text study with a content analysis method which focuses on discussing the content of written or printed information in the media. Content analysis is used to examine data in order to gain an understanding and present facts objectively. The content used in this research is a book of short stories entitled Cerpen Pilihan Kompas 2021. The research object is the hypocrisy depicted by the author through the story. This short story shows that hypocrisy is not only a reflection of individual character but also a consequence of broader social conditions. Social injustice and poverty contribute to moral decline, illustrating how society compromises moral values ​​in the face of economic pressures and injustice. The findings show that hypocrisy is not only a reflection of individual character. It is also a consequence of broader social dynamics showing moral decline in society due to economic pressure and injustice.